Cryptocurrency as a Medium of Rupiah Exchange: Perspective Sharia Islamic Law and Jurisprudential Analysis - Asyiqin, Istianah Zainal; Akbar, M. Fabian; Beltrán Genovés, Manuel (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
The rapid advancement of the digital age has driven significant developments in payment systems, influencing financial decisions and fostering economic activity. This study explores the use of cryptocurrencies as digital currencies in financial transactions, particularly in the context of investments, while assessing their compatibility with Islamic law. Employing a normative legal approach and a descriptive-analytical method, the research examines legal principles and facts concerning cryptocurrency regulation in Indonesia. The findings reveal that, despite the potential benefits of cryptocurrencies, their usage remains contentious from both regulatory and Islamic law perspectives. In Islamic law, cryptocurrency transactions are classified as haram lighairihi due to elements of uncertainty (gharar) and speculative risks, making them non-compliant with Sharia principles. As a solution, this study proposes a framework for integrating cryptocurrency exchanges with Rupiah transactions in accordance with Sharia economic principles. This integration aims to mitigate risks while maintaining the flexibility of digital transactions, ensuring they align with both regulatory standards and Islamic legal frameworks.